Passivity-based adaptive current control loop of cascaded H-bridge multilevel converter for grid-tied photovoltaic system - Cuong, Tran Hung; Thu Anh, An Thi Hoai (Institute of Advanced Engineering and Science, 2024)
This paper proposes an algorithm to passivity-based control (PBC) for the current control loop of the cascaded H-bridge converter (CHB) connecting the grid-connected PV system with the space vector modulation (SVM) algorithm using the law of expanding any number of voltage levels. The algorithm SVM in this paper is suitable for CHB converters. It can create a number of high levels of alternating voltage that other methods cannot do. Passivity-based control (PBC) algorithm aims to create a flexible controller that can change its structure or parameters to adapt to changes in the system, ensuring stable system quality, reducing switching losses and gaining energy conversion efficiency. It enhances the capability of accurately delivering power on demand to the grid with the CHB inverter in situations in which the grid demands the mobilization of maximum power from the photovoltaics (PV) system. The simulation results of the 9-level CHB system performed by MATLAB/Simulink software have proved the feasibility of the proposed algorithm.